Size variations and correlation of different cell cycle events in slow-growing Escherichia coli. - Koppes, L H (1978)
Cell lengths have been determined at which cycle events occur in the slow-growing Escherichia coli B/r substrains A, K, and F26. The radioautographic and electron microscope analyses allowed determination of the variations in length at birth, initiation and termination of DNA replication, and initiation of the constriction process and of cell separation. In all three substrains the standard deviation increased between cell birth and initiation of DNA replication. From there on, the standard deviation remained relatively constant until cell separation. These observations are consistent with the presence of a deterministic phase during the cell cycle in which the cell sizes at initation of DNA replication and at cell division are correlated.